2021
DOI: 10.3389/fenrg.2021.742109
|View full text |Cite
|
Sign up to set email alerts
|

Two Sides of the Same Coin—Explaining the Acceptance of CO2-Based Fuels for Aviation Using PLS-SEM by Considering the Production and Product Evaluation

Abstract: In the present study, we studied the acceptance of CO2-based fuels for aviation as a product manufactured using Carbon Capture and Utilization (CCU). CCU can be regarded as the cornerstone for a circular approach. We focused on understanding whether the evaluation of CCU as a production method is related to the social acceptance of the resulting product. We applied an empirical quantitative approach using an online questionnaire targeted at German, Spanish, Dutch, and Norwegian respondents (N = 2,187). For bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…The most significant factor influencing the readiness for CO 2 -based aviation fuels was the subjective evaluation of CO 2 -based aviation fuels based on risk and benefit perceptions (H6.1a/b and H6.2 a/b supported). With increased risk perceptions regarding environmental and health risks as well as regarding technical quality and maturity of CO 2 -based aviation fuels, acceptance and the behavioral intention were lowered (corresponding to Arning et al, 2019;Simons et al, 2021b). As the descriptive analysis showed, risk perceptions were not elevated with respect to environmental and health risks, but there were elevated risk perceptions with respect to product quality and technical maturity of CO 2 -based aviation fuels.…”
Section: What Drives Social Readiness Of Co 2based Aviation Fuels?mentioning
confidence: 97%
See 1 more Smart Citation
“…The most significant factor influencing the readiness for CO 2 -based aviation fuels was the subjective evaluation of CO 2 -based aviation fuels based on risk and benefit perceptions (H6.1a/b and H6.2 a/b supported). With increased risk perceptions regarding environmental and health risks as well as regarding technical quality and maturity of CO 2 -based aviation fuels, acceptance and the behavioral intention were lowered (corresponding to Arning et al, 2019;Simons et al, 2021b). As the descriptive analysis showed, risk perceptions were not elevated with respect to environmental and health risks, but there were elevated risk perceptions with respect to product quality and technical maturity of CO 2 -based aviation fuels.…”
Section: What Drives Social Readiness Of Co 2based Aviation Fuels?mentioning
confidence: 97%
“…By now, there are a few studies that empirically examine the public perception of the CCU technology, its production processes, and of CO 2 -based products such as fuels. In a direct comparison between the perception of the technological infrastructure and of CO 2 -based products, the CCU technology infrastructure has been judged positively but still worse than the final CO 2 -based fuel product (van Heek et al, 2017;Arning et al, 2019;Simons et al, 2021b). Considerable differences also exist between socio-political acceptance judgments related to the overall concept of CCU in terms of a climate-mitigation option and the local acceptance of CCU systems that would be implemented in the immediate neighborhood (Arning et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides an active acceptance or rejection of a technology, individuals can also adopt an indifferent position, where no attitude has been developed yet (Arning et al, 2019). Furthermore, it was shown that social acceptance reactions towards CO 2 -based products are not only relevant when it comes to marketable end products (Arning et al, 2021;Simons et al, 2021b), but the production process was also impacted by acceptance factors (Camacho-Otero et al, 2019;Evans, 2019;Simons et al, 2021a). Apparently, consumers do not only consider the final product but try to gauge the way it is produced.…”
Section: Public Perception and Acceptance In The Context Of Renewable...mentioning
confidence: 99%
“…However, public acceptance is a fragile good which needs to be formed and publicly developed with care. The intention to use a novel product, as general part of public acceptance, requires information and knowledge about the product and the production in order to allow informed decisions for using these novel products (cognitive component) (van Heek et al, 2017b;Linzenich et al, 2019;Offermann-van Heek et al, 2020) on the one hand and affective components, for example, trust in the product and the production process, a balanced and informed risk handling towards the novel production routes, and the product quality (van Heek et al, 2017a;Arning et al, 2020;Simons et al, 2021a) on the other hand. Before effective and acceptance-related information and communication strategies can be developed, an understanding of the public's attitudes and the factors underlying acceptance and risk perceptions need to be assessed (Jones et al, 2017;Arning et al, 2018;Simons et al, 2021a).…”
mentioning
confidence: 99%
“…This integration of the public in early phases of technology development is a necessary requirement of forming shared common values [e.g., (Pelletier et al, 1999)] and also fosters the trust in the transparency of the process, the information, and the public authority [e.g., (Offermannvan Heek et al, 2018;Kluge et al, 2021)]. In addition, one should be aware that the group of laypeople is not limited to the general public, but also includes many people in policy, institutions, and governance, who are in charge of taking such far-reaching infrastructure decisions [e.g., (Offermann-van Heek et al, 2018;Kluge et al, 2021;Simons et al, 2021)]. Therefore it seems to be a mandatory claim of fair decisionmaking for renewable infrastructure decisions that the lay public is not only transparently informed during the technical development process, but rather, that acceptance factors and public perceptions are studied in line with the conceptualization and the design of infrastructure technology.…”
Section: Practical Implications: Guidelines For Decision Makersmentioning
confidence: 99%